2023
DOI: 10.1177/00469580221146830
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Limited Access to Care for Community-Based Patients With Spinal Cord Injury and Stroke in Nepal and the Potential of Telerehabilitation: A Qualitative Study

Abstract: This study explores the experiences of care received and management of disability for individuals with spinal cord injury and stroke following discharge from a specialty rehabilitation center, alongside perspectives on the potential role of telerehabilitation. We employed qualitative in-depth face-to-face interviews with patients who had accessed and been discharged from a specialist rehabilitation center in Nepal were used. Interviews sought perspectives of adjusting to, living with, and managing disability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The specific nature of the intervention may have contributed to preventing or minimizing the occurrence of these complications, thus demonstrating its effectiveness in promoting better health outcomes. The findings from our study also corroborate the existing literature [ 16 , 17 ]. Recent systematic reviews and meta-analyses also revealed that, though telerehabilitation is found to improve certain domains of neurological disorders, it needs more evidence [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The specific nature of the intervention may have contributed to preventing or minimizing the occurrence of these complications, thus demonstrating its effectiveness in promoting better health outcomes. The findings from our study also corroborate the existing literature [ 16 , 17 ]. Recent systematic reviews and meta-analyses also revealed that, though telerehabilitation is found to improve certain domains of neurological disorders, it needs more evidence [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nepal has consistently faced financial hardship as the most critical barrier to health care services, including rehabilitation (Shah et al, 2013). Other key barriers to rehabilitation in Nepal include challenging topography, limited availability of transportation facilities (Baniya et al, 2023), limited knowledge related to rehabilitation among the public, and a shortage of rehabilitation professionals (Shah et al, 2013). Similarly, the political turmoil of the nation might have kept the development of rehabilitation policies at bay.…”
Section: Rehabilitation Services In Nepalmentioning
confidence: 99%